Adição de resíduo de casca de eucalipto em matriz de pvc com diferentes concentrações e tamanhos: caracterização do resíduo e do compósito - Scapolio, Luiz Guilherme Barbin (Universidade Federal de São Carlos, 2020)
Brazil is the largest producer of short fiber cellulose worldwide, mainly obtained from eucalyptus, which is a fast-growing tree. Due to this high production of cellulose, large amounts of eucalyptus bark residues (EBR) are generated, which, because it is a low-cost material, was chosen as the theme of this work, verifying the possibility of using, adding value to it. Thus, the influence of the addition of ground EBR with different sizes of granulometry - between 75μm and 250μm and between 300μm to 850μm - was evaluated as a load in a PVC matrix in the range of 10 to 40 phr, aiming to obtain composites known as plastic wood. The processing method used was calendering, followed by hot pressing. To understand the residue, chemical analysis, thermogravimetric analysis (TGA), scanning electron microscopy (SEM) and length-by-diameter (L/D) tests were performed. With the composite were carried out tests of density, tensile, flexural, impact, heat deflection temperature (HDT), moisture absorption and SEM of the fracture tensioned samples. Acicular and irregular shapes were observed in the fillers, as well as the presence of calcium oxalate. In relation to composites, improvements were obtained for the tensile and flexural modulus with the increase in the amount of filler added, wherein the fibers of smaller particle size showed a small positive difference in relation to those of larger particle sizes, however there was a decrease in elongation at break and impact resistance. With SEM it was possible to verify the detachment and pull-out of the fibers in tensile, showing their low adhesion to the matrix. Thus, the use of EBR proved to be possible, however, adjustments in the processing are still necessary to reach the proper properties, investigating the effects of compatibilizers and aging on the composite.
Addition of eucalyptus bark residue in pvc matrix with differents contents and sizes: characterization of residue and composite
Keywords: WPC; PVC/resíduo de casca de eucalipto; Compósitos; Fibras naturais; PVC/eucalyptus bark residue; Composites; Natural fiber; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS